Unlocking Ancient Remedies: Berberis Aristata Extract as a Lead Candidate, Exploring the Potential of Indian Sarsaparilla for Combating Drug-Resistant Bacteria - Sakpal, Prerana; Bansode, Ankita S.; Mhatre, Sanjivani; Hamza, Ameer; Chormale, Abhijeet; Pandey, Satyam (Asian Journal of Pharmaceutical Research and Development, 2024)
The emergence of drug-resistant bacteria poses a significant threat to global health. This study investigated the potential of plant extracts as a source of novel antibacterial agents. The antibacterial activity of various plant extracts was evaluated against common pathogenic bacteria, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. Among the tested extracts, Berberis aristata (sample 3) and Indian sarsaparilla (sample 4) displayed notable broad-spectrum antibacterial activity. Minimum Inhibitory Concentration (MIC) determination using the Resazurin Microtiter Assay (REMA) revealed the superior potency of Berberis aristata compared to Indian sarsaparilla. This finding suggests that Berberis aristata extract exhibits antibacterial activity at lower concentrations, highlighting its potential for further development as a therapeutic agent. These results highlight Berberis aristata as a promising natural source for the development of novel broad-spectrum antibacterial agents to combat drug-resistant bacteria. Further research is warranted to elucidate the mechanisms of action of Berberis aristata and to assess its efficacy and safety in vivo models. Additionally, establishing standardized extraction protocols and quality control measures is necessary for consistent results and future therapeutic applications.